The Effectiveness of Local Wisdom-Based English Reading Teaching Materials in Improving Reading Literacy of Deaf Students - Miranti Eka Putri (Journal of Languages and Language Teaching, 2023)
This research is motivated by the problem of the reading literacy of deaf students, who are still relatively weak. This study aims to determine the effectiveness of local wisdom-based English reading teaching materials on improving the reading literacy of deaf students in class XI SMALB. This type of research uses a quantitative approach with an experimental research design. The sample for this study used the purposive sampling technique; the research sample was in class XI with 25 students. Data collection techniques include tests and documentation. Instrument testing uses validity and reliability. Data analysis techniques include descriptive analysis and pre-requisite tests, namely the normality test, hypothesis test, and N-Gain test. Based on data processing, the results of the study show that English reading teaching materials based on local wisdom effectively improve the reading literacy of deaf students. This is evidenced by the results of the sig value of 0.000> 0.05; thus, it can be said that there is an increase in reading literacy with local wisdom-based English reading teaching materials, which are in the high category, where the N-Gain value is 0.76.